Blood lactate minimum of rats during swimming test using three incremental stages - Mariana de Souza Sena; Roberto Carlos Vieira Junior; Cássio Charnoski Rubim; Thiago da Rosa Lima; Joice Cristina dos Santos Trombeta; Alesandro Garcia; Jonato Prestes; Ramires Alsamir Tibana; Fabrício Azevedo Voltarelli (Motriz: Revista de Educacao Fisica, 2015)
AbstractThe purpose of this study was to determine the lactate minimum intensity (LMI) by swimming LACmintest using three incremental stages (LACmintest3) and to evaluate its sensitivity to changes in aerobic fitness (AF). Twenty Wistar rats performed: LACmintest3 (1): induction of hyperlactacidemia and incremental phase (4%, 5% and 6.5% of bw); Constant loads tests on (2) and above (3) the LMI. Half of the animals were subjected to training with the individual LMI and the tests were performed again. The mean exercise load in LACmintest3 was 5.04 ± 0.13% bw at 5.08 ± 0.55 mmol L-1 blood lactate minimum (BLM). There was a stabilize and disproportionate increase of blood lactate in tests 2 and 3, respectively. After the training period, the mean BLM was lower in the trained animals. The LACmintest3 seems to be a good indicator of LMI and responsive to changes in AF in rats subjected to swim training.